Literary Representation of Racism and Civil War in Somalia: A Textual Study of Nuruddin Farah’s Cross Bones - Bilal Ahmad Dar (The Creative Launcher, 2017)
Somalia, a country in the Horn of Africa; is wrought with multiplex conflictive issues like dictatorship, clan conflagrations, tribal animosity, and racial altercations. The menace of racism, dictatorship, tribalism and other aligned issues have rendered Somalia economically hollow, politically unstable, and volatile in the context of overall conditions. Racism in the shape of clannish skirmishes and communal confrontations in Somalia is one of the obnoxious and detrimental issues that have made it a failed state. Many writers have depicted this issue of racism through their writings. Nuruddin Farah is one of the outspoken Somalian novelists who dauntlessly denigrate racism in Somalia through his novels. Nuruddin Farah is a very prolific novelist. He has many novels to his credit that contain issues of patriarchal oppression, gender inequality, and racism. The paper attempts to show through the textual study of the novel how Nuruddin Farah projects racism and civil war in Somalia through his much acclaimed and polemical novel Cross Bones.